TINGKAT MOTIVASI TERHADAP PERILAKU WIRAUSAHA PETERNAK BROILER POLA KEMITRAAN CONTRACT FARMING DI KOTA PEKANBARU - Siti Sukmawati Maimanah; Cepriadi Cepriadi; Rosnita Rosnita (Fakultas Pertanian, Universitas Riau, 2018)
This study aimed to analyze the level of motivation and behavior level of broiler breeders in Pekanbaru City. The method used in this research was survey method. The respondent selection technique was conducted by convenience sampling. Respondents were rural chicken breeders who work together / as partner in a contract farming pattern with a partner company in Pekanbaru. The data collected in this study was of primary and secondary data. The results showed that the motivation of respondents in this study has an average of 3.81 with the category of motivated, which meant intrinsic and extinsic motivation affect broiler breeders in an effort. The biggest indicator that affects the award with an average of 4.83 with the category highly motivated and the lowest is achievement indicator with an average of 2.14 with the less motivated category, and Level of behavior of broiler breeder showed average value of 3.58 with good respondent behavior category. Responsiveness to opportunities was the highest indicator that affects employers’ behavior of 4.77 which meant very good, while the lowest was dare to take risks with a value of 2.03 with the less good category.